Endocrine Complications in Langerhans Cell Histiocytosis: A Case of Empty Sella Syndrome with Hypopituitarism - Rizqi Rifani; Tri Juli Edi Tarigan (PP PERKENI, 2025)
Langerhans cell histiocytosis (LCH) is a rare clonal myeloid neoplasia characterized by infiltration of CD1a+/CD207+ dendritic cells, frequently affecting bones, skin, and the central nervous system. Endocrine complications, particularly involving the hypothalamic-pituitary axis, are common in multisystem disease and may result in irreversible dysfunction, impacting growth, development, and overall quality of life. Case Presentation: An 18-year-old male diagnosed with LCH at age 10 presenting with polyuria, polydipsia, and delayed puberty. He was found to have central diabetes insipidus, central hypothyroidism, hypogonadotropic hypogonadism, and a grade IV empty sella on brain MRI. The patient had a history of bone and soft tissue involvement and underwent chemotherapy for multisystem LCH. His current therapy includes desmopressin, levothyroxine, vitamin D, calcium supplementation, and planned to given testosterone replacement. This case illustrates the classic progression of endocrine complications in LCH with hypothalamic-pituitary axis involvement. Central diabetes insipidus is often the first manifestation followed by anterior pituitary hormone deficiencies. The finding of total empty sella on MRI likely reflects chronic inflammatory damage or pituitary atrophy. The combination of central diabetes insipidus (CDI), central hypothyroidism, and delayed puberty requires lifelong hormonal replacement and regular endocrine follow-up. The case also highlights the importance of addressing bone health and growth delays secondary to hormonal deficiencies and previous glucocorticoid therapy. Early identification and management of endocrine complications in LCH, particularly those involving the pituitary are essential to reduce morbidity and improve patient outcomes. Lifelong monitoring and multidisciplinary care are necessary for optimal management of LCH survivors.